Histoplasmosis in an immunocompetent host: a rare case report - Kriplani, Dipsha M.; Kante, Katha A.; Maniar, Janak K.; Khubchandani, Shaila R. (International Journal of Research in Medical Sciences, 2017)
Histoplasmosis, a systemic mycosis caused by Histoplasma capsulatum manifests clinically in immunocompromised patients as acute or chronic pulmonary infection or as a progressive disseminated disease. In immunocompetent hosts, the disease is usually self-limited or presents as flu-like symptoms. It is endemic in North, Central and South America as well as parts of Europe and Africa. We report a case of a 76-year-old diabetic, HIV negative patient who presented with white nodular patches on the tongue and gingiva which were reported as histoplasmosis on histopathology. He also had idiopathic CD4 lymphocytopenia and thrombocytopenia.